Flat Stanley : Stanley, flat again! - Brown, Jeff, 1926-2003.; Pamintuan, Macky (New York : Harper, 2009)
After Stanley Lambchop goes flat once again, he uses his flatness to help win a sailboat race and to rescue a classmate from a collapsed building.
Booklist
Horn Book
School Library Journal
Booklist, May 2003
Horn Book, April 2004
School Library Journal, March 2003
Keywords: Lambchop, Stanley -- (Fictitious character) -- Juvenile fiction; Lambchop, Stanley -- (Fictitious character) -- Fiction; Lambchop, Stanley -- (Fictitious character) -- Fiction; Sailing -- Juvenile fiction; Humorous stories; Sailing -- Fiction; Humorous fiction; Sailing -- Fiction; Humorous fiction